Morphology-dependent immunomodulatory coating of hydroxyapatite/PEO for magnesium-based bone implants - Farshid, Safoura; Kharaziha, Mahshid; Salehi, Hossein; Ganjalikhani Hakemi, Mazdak (My University, 2023)
One of the most critical issues concerning orthopedic implants is the risk of chronic inflammation, which poses a threat to the bone healing process. Osteo-immunomodulation plays a pivotal role in implant technology by influencing proinflammatory and anti-inflammatory responses, ultimately promoting bone healing. This study aims to investigate the morphology-dependent osteo-immunomodulatory properties of a hydroxyapatite (HA)/plasma electrolytic oxidation (PEO)-coated WE43 alloy. In this context, following the PEO process with various operational parameters (duty cycles of 50-40, 50-20, 70-40%, and frequencies of 0.5, 0.8, and 1 kHz), a layer of HA was applied as the top coating using a straightforward hot-dip process. The results revealed the formation of the PEO layer with distinct morphologies and pore sizes, depending on the operational parameters. Specifically, a uniform PEO coating with small pore sizes (5.2-5.3 ?m) led to the creation of plate-like HA particles, while a random-like HA structure formed on nonuniform surfaces with large pores (7.0-11.1 ?m) of PEO. Moreover, it was observed that the plate-like HA coating exhibited higher adhesion strength than the random one (classified as class 2 vs class 3 based on cross-cut standards). Furthermore, electrochemical impedance spectroscopy (EIS) and polarization studies confirmed a substantial increase in the polarization resistance (680 k?) and total impedance (48?559.6 ?) for the plate-like HA/PEO as compared to the substrate (an increase of 1511-fold and 311-fold, respectively) and the random HA/PEO samples (an increase of 85-fold and 18-fold, respectively). In addition, compared to random HA coatings, there was a significant enhancement in the viability (150% control vs 96% control), proliferation, and differentiation of MG63 cells when exposed to plate-like HA coatings. Moreover, surface morphology and chemistry pronouncedly impacted macrophages' viability, morphology, and phenotype. Notably, plate-like HA coatings resulted in a higher upregulation of BMP-2 and TGF-? than proinflammatory cytokines (IL-6 and M-CSF), indicating a polarization of macrophage type 1 (M1) toward type 2 (M2). In summary, the bilayer HA/PEO coating exhibited remarkable osteo-immunomodulatory activity, making it highly appealing for use in bone implant applications.
Keywords: Hydroxyapatite; Immunomodulation Activity; Magnesium Alloy; Orthopedic Implant; Plate-Like Morphology